On the solvability of discrete nonlinear Neumann problems involving the p(x)-Laplacian - Guiro, Aboudramane; Nyanquini, Ismael; Ouaro, Stanislas (Advances in difference equations, 2011)
In this article, we prove the existence and uniqueness of solutions for a family of discrete boundary value problems for data f which belongs to a discrete Hilbert space W . 2010 Mathematics Subject Classification: 47A75; 35B38; 35P30; 34L05; 34L30.